Evaluasi Usability Antarmuka Instagram pada Mahasiswa - Arini Sastra Marulafau; Mahda Khairun Nazwa Daulay; Rafika Hadi Siregar; Syukri Falahi Capah; M. Khalil Gibran (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This study examines the usability of Instagram’s interface among university students since Instagram has become one of the social media platforms most frequently used in daily life and academic activities. The study aims to find out how easy and comfortable Instagram is to use based on Nielsen’s usability dimensions which include learnability, memorability, efficiency, error prevention, and satisfaction. This research used a descriptive quantitative method by distributing a 5-point Likert scale questionnaire to 76 active university students in May 2026. The results showed that the overall usability score reached 3.88 and was categorized as “Good”. The satisfaction dimension obtained the highest score of 3.98 while error prevention received the lowest score of 3.75. The findings also revealed that some students were still confused by the similarity between the Reels and Explore features while the placement of advertisements was considered disruptive to navigation. In addition, many respondents suggested adding a study focus mode to support productivity while using Instagram. Overall, Instagram already provides a good usability experience, although improvements are still needed in navigation consistency, error prevention, and features that better support student needs.